2016
DOI: 10.1155/2016/7109270
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Updated Review of Pharmaceutical and Nonpharmaceutical Treatment for NAFLD

Abstract: Nonalcoholic fatty liver disease (NAFLD) is the most common liver disease in the western world with prevalence of 20–33%. NAFLD comprises a pathological spectrum. Nonalcoholic fatty liver (NAFL) is at one end and consists of simple hepatic steatosis. On the contrary, nonalcoholic steatohepatitis (NASH) consists of steatosis, inflammation, and ballooning degeneration and can progress to cirrhosis. Despite the rising incidence, definitive treatment for NAFLD, specifically NASH, has not yet been established. Life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 183 publications
0
35
0
3
Order By: Relevance
“…Nevertheless, it is noteworthy that, to date, no specific therapy has been approved for NASH. [5][6][7][8] Phyllanthus niruri, a herb extensively used in traditional Malay, Chinese and Ayurvedic medicine, is a potential therapeutic agent for a wide range of liver diseases, as laboratory studies have confirmed its antiviral, anti-inflammatory, antioxidant and hepatoprotective properties. [9][10][11][12][13] However, it has never been tested in patients, particularly those with NASH.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it is noteworthy that, to date, no specific therapy has been approved for NASH. [5][6][7][8] Phyllanthus niruri, a herb extensively used in traditional Malay, Chinese and Ayurvedic medicine, is a potential therapeutic agent for a wide range of liver diseases, as laboratory studies have confirmed its antiviral, anti-inflammatory, antioxidant and hepatoprotective properties. [9][10][11][12][13] However, it has never been tested in patients, particularly those with NASH.…”
Section: Introductionmentioning
confidence: 99%
“…Nonalcoholic fatty liver disease (NAFLD) has become the most common cause of liver disease and abnormal liver function test in industrialized countries [15] with prevalence of 20-33% [3]. There is lower prevalence and lower degree of liver cell injury in African American population while higher prevalence is reported in Asians and Hispanics with advanced grade of liver damage compared to other ethnicities [16].…”
Section: Global Epidemiology Of Hepatitis B and Fatty Livermentioning
confidence: 99%
“…Prevalence of HBV among children and adult both has been decreased than previous time. Nonalcoholic fatty liver disease (NAFLD) has become the most common cause of liver disease with prevalence of 20-33% [3]. In the Asia-Pacific region the prevalence of NAFLD has increased remarkably over the years affecting up to 30% of the general population [4].…”
Section: Introductionmentioning
confidence: 99%
“…Contrarily, concerns about vitamin E long-term safety exist as it may be associated with increased risk for cardiovascular events and prostate cancer in older patients >50years. 89 Obeticholic acid, which is a synthetic farnesoid X receptor agonist, decreased IR in T2DM and improved all NASH lesions and fibrosis in non-cirrhotic NASH patients after 72weeks of treatment.…”
mentioning
confidence: 99%
“…However, not many studies have been done in humans with NAFLD to assess the effectiveness of ACE inhibitors or angiotensin receptor blockers. 89 …”
mentioning
confidence: 99%